Carbon monoxide and mitochondria—modulation of cell metabolism, redox response and cell death - Almeida, Ana S.; Figueiredo-Pereira, Cláudia; Vieira, Helena L. A. (Frontiers in Physiology, 2015)
Carbon monoxide (CO) is an endogenously produced gasotransmitter, which is associated with cytoprotection and cellular homeostasis in several distinct cell types and tissues. CO mainly targets mitochondria because: (i) mitochondrial heme-proteins are the main potential candidates for CO to bind, (ii) many CO's biological actions are dependent on mitochondrial ROS signaling and (iii) heme is generated in the mitochondrial compartment. Mitochondria are the key cell energy factory, producing ATP through oxidative phosphorylation and regulating cell metabolism. These organelles are also implicated in many cell signaling pathways and the production of reactive oxygen species (ROS). Finally, mitochondria contain several factors activating programmed cell death pathways, which are released from the mitochondrial inter-membrane space upon mitochondrial membrane permeabilization. Therefore, disclosing CO mode of action at mitochondria opens avenues for deeper understanding CO's biological properties. Herein, it is discussed how CO affects the three main aspects of mitochondrial modulation of cell function: metabolism, redox response and cell death.